255 Efficacy of sequential immune checkpoint inhibition (ICI) in patients with genitourinary malignancies. (9th November 2020) - Evans, Sean; Martini, Dylan; Magod, Benjamin; Olsen, Timothy; Brown, Jacqueline; Yantorni, Lauren; Ravindranathan, Deepak; Russler, Greta; Caulfield, Sarah; Goldman, Jamie; Nazha, Bassel; Harris, Wayne; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI) have become a standard of care for treatment of both metastatic renal cell carcinoma (mRCC) and metastatic urothelial carcinoma (mUC). Additional treatment with ICI following disease progression on first-line therapy has become increasingly common for patients with severe disease, but the clinical outcomes of sequential therapy have not been well studied. We report here the clinical outcomes in a cohort of patients with mRCC and mUC who received two regimens of ICI-based therapy. Methods: We performed a retrospective review of 31 mRCC patients and 11 mUC with follow-up data available who received at least 1 dose of a 2nd ICI-based regimen at the Winship Cancer Institute of Emory University from 2015–2020. Radiographic responses were determined using response evaluation criteria in solid tumors version 1.1 (RECISTv1.1). An objective response (OR) was defined as a complete response (CR) or partial response (PR). Clinical benefit (CB) was defined as an objective response or stable disease (SD) > 6 months. Results: Most patients were white (81%) and male (69%). 31 had mRCC (table 1) and 11 had mUC (table 2). Overall most patients (58%) received anti-PD-1 (Programmed cell death protein 1) monotherapy as first line, with anti-PD-L1 (Programmed death-ligand 1) monotherapy (33%) and anti-PD-1/CTLA-4 (Cytotoxic T-lymphocyte-associated protein 4) combination therapy (9%) being less prevalent. Patients spent an average of 27.1 weeks on first ICI therapy. Second ICI-based treatment was most commonly anti-PD-1/CTLA-4 (62%), followed by anti-PD-1 monotherapy (38%). A subset of patients (33%) had clinical benefit with combination anti-PD-1/CTLA-4-based second ICI therapy, with 4 (10%) having PR and one (2%) having CR of disease following second ICI-based treatment. Patients spent an average of 21.4 weeks on the second ICI regimen. The response rate for the entire cohort was 11.9% (16.7% for RCC and 0% for UC).The CB rate for the entire cohort was 40% (40% for RCC and 40% for UC). Immune-related adverse events were experienced in a subset of patients (28%). Conclusions: Although we observed a low OR rate to a second ICI-based regimen, a select subset of patients did have CB from a second ICI-regimen. Current studies exploring the addition of CTLA4 inhibitors to anti-PD-1 therapy may provide insight into the greater efficacy of treatment within a subset of patients. Further analysis of a larger cohort receiving sequential immunotherapy is necessary to better identify patients who may be more likely to derive CB from sequential ICI. Ethics Approval: This retrospective study was approved by the Emory University Institutional Review Board. Consent: Not applicable. Acknowledgements: Research reported in this publication was supported in part by the Breen Foundation. Trial Registration: Not applicable. References: Not applicable